Influence of Morphological Awareness on College Students' Literacy Skills: A Path Analytic Approach. (September 2015) - Wilson-Fowler, Elizabeth B.; Apel, Kenn
The purpose of this study was twofold: to create a measure of morphological awareness with college students and to examine effects of morphological awareness on literacy abilities. Three morphological awareness measures, and spelling, word reading, and sentence comprehension tasks were administered to 214 undergraduate college students. Item Response Theory analyses generated a 24-item, validated morphological awareness measure. Path analysis revealed that morphological awareness was a strong predictor of spelling with a standardized path coefficient of .77, and a moderate predictor of word reading and sentence comprehension, with standardized path coefficients of .62 and .58, respectively. Both spelling and word reading were partial mediators of relations between morphological awareness and sentence comprehension. The standardized indirect effect of morphological awareness on sentence comprehension was .38 through spelling and .13 through word reading. A valid morphological awareness measure now exists for use with college students. Morphological awareness is a stronger predictor for spelling than for word reading and sentence comprehension.